The Analysis of the Positive Patterns in Education - Lin Liu; Yong Liu; Tao Wang; Yanxia Liu (Journal of Linguistics and Communication Studies, 2023)
Each individual is responsible for his or her own actions. Parents should guide their children to be responsible for their own behavior, but also take responsibility for their children actively. Through positive family education, parents engage in growth and reflection. With family education like this, parents get the result twice with half the effort. Parents need to actively seek out and use the positive patterns in the guide of family education. Parents need to find the root of the problem in family education and guide their children to grow up positively and healthily. The positive guide of family education can encourage more parents to take family education seriously and effectively.